2019
DOI: 10.1159/000501034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus on Postoperative Complications Following Laparoscopic Hysterectomy for Benign Indications

Abstract: <b><i>Background:</i></b> Current research pertaining to minimally invasive gynecologic surgical outcomes in the context of diabetes mellitus (DM) is limited. This study seeks to evaluate the association between DM and postoperative complications following laparoscopic hysterectomy for benign indications. <b><i>Methods:</i></b> The American College of Surgeons National Surgical Quality Improvement Program database was utilized. We identified laparoscopic hysterec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…Therefore, it is necessary to measure and control FBS levels in those undergoing surgery. These results are in line with the findings of Corrigan et al (22), Jiamset et al (23), and Fakhari et al (11).…”
Section: Laboratory Testssupporting
confidence: 93%
“…Therefore, it is necessary to measure and control FBS levels in those undergoing surgery. These results are in line with the findings of Corrigan et al (22), Jiamset et al (23), and Fakhari et al (11).…”
Section: Laboratory Testssupporting
confidence: 93%
“…[21][22][23][24][25][26][27][28] Age, BMI, diabetes and indication for surgery have all been shown to influence complications. 11,25,27,[29][30][31] Uterine weight has also been shown to influence outcomes; 11,29,32 however, we did not include it because it would not be available preoperatively. The gynecologic diagnoses were chosen as they represent most benign indications at the time of hysterectomy.…”
Section: Predictorsmentioning
confidence: 99%
“…29 We identified clinical predictors for conversion from ICD-10 codes for obesity and diabetes. 31 Common gynecologic diagnoses recorded at the time of hysterectomy were identified from ICD-10 codes and include fibroids, menstrual disorders, endometri osis and pain, adenomyosis and benign adnexal mass. Women may have more than 1 gynecologic diagnosis at the time of hysterectomy.…”
Section: Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, numerous studies have shown that frailty, a syndrome that is characterised by the loss of biological reserves and mounting failure of homeostatic mechanisms and that manifests mainly in the elderly, is often The positive association in our analysis between diabetes and donor-site complications is backed by the literature. A number of publications assert a positive association between diabetes and postoperative complications in different abdominal surgeries [31,32]. This is hardly surprising, since metabolic syndrome-a constellation of hyperglycaemia, hypertension, dyslipoproteinemia, and truncal obesity-is considered an important risk factor for morbidity and has not without reason been nicknamed "the deadly quartet" [33].…”
Section: Donor-site Complications: Presumed Causes and Impactmentioning
confidence: 99%